O mutante e o mercador : direitos fundamentais e contratos envolvendo novas técnicas biológicas - Hartmann, Ricardo Marchioro (2015)
The technology is old as humanity. The human being is technological. The society is technological. Never experienced a time as linked with the future as nowadays. The reality is constantly remodeled, encompassing not mere spectators, but true protagonists. Civilization is intertwined with exciting new interrogations particularly linked to Biotechnology. New techniques in the field of biology, which in many cases are applied on human life and ultimately influence directly in their most intimate rights. Technologies which nurture a complexity of relationships between private individuals, including exposing new contractual niches. Topping a new contractual object consistent in the vivant. It presents a new and multifaceted reality to which the private law, from a modern vision, do not offer an appropriate treatment. We live in an outdated contract law. Extract that only a civil law centered in human being and constitutionalized allows to track the reality. It is observed that in a legal system, with constitutional epicenter, the human dignity, the fundamental rights and the rights of personality embody the tools for formatting and interpretation of law. Moving away from the constraints of modernity, in which there were hard-fixed solutions to the situations experienced in the day-to-day, assuming that overriding a systematic topic analysis. Is attained, from a new perspective of reflection and interpretation, that rights taken as absolute can be relativized, since it´s justified by the application of fundamental rights in this case - always seeking the concretion of human dignity. Culminating in viability, depending on the experienced situation, the human body disposal, including through costly biotechnological contracts.